Visible-light photoredox enables ketone carbonyl alkylation for easy access to tertiary alcohols - Vu, Minh Duy (2020)
Being a handle for synthesizing quaternary carbon centers and olefins, together with ubiquitous appearance in organic building blocks, makes tertiary alcohols valuable targets in synthesis. However, traditional syntheses of these alcohols have faced several challenges including the employment of functionalized reactive reagents, undesirable side reactions, and decomposition of the alcohol products under harsh conditions. The paucity of a synthetic approach to bulky tertiary alcohols prompts our interest to develop a benign catalytic protocol to tackle the current issues. Here, we have successfully demonstrated the use of ketyl radicals in intermolecular cross radical-radical coupling, which has opened a different door for accessing complex tertiary alcohols. On the other hand, by starting from feedstock and naturally derived chemicals without any pre-activation, it would be superior to traditional methodologies in the industrial context.